2002
DOI: 10.1063/1.1502650
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies of CIDNP kinetics in recombination of radical pairs by the method of switched external magnetic field. III. Free radicals in homogeneous solution

Abstract: The method of chemically induced dynamic nuclear polarization in a switched external magnetic field (SEMF CIDNP) is applied here for the first time to an experimental study of short-lived neutral radicals in homogeneous solutions. With three photochemical reactions it is exemplified, that SEMF CIDNP allows investigations of the kinetics of the transient species with high time-resolution as well as a determination of their spin relaxation times in low magnetic fields. A theoretical approach is developed, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In particular, for several methyl-containing compounds with hindered rotation of the CH 3 group Ellis et al [37] found a nearly linear relationship between TI,SR and the potential barrier V 0 of the rotation from 13C relaxation measurements at fixed temperature (38~ T1,sR = 25.61 (1 + 0.382 V0), (5) where T1.sR is given in seconds and V 0 is the barrier height in kilocalories per mole, determined by microwave spectroscopic methods. The relation is remarkable in view of the variety of compounds involved, with reported barriers as high as 5.4 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for several methyl-containing compounds with hindered rotation of the CH 3 group Ellis et al [37] found a nearly linear relationship between TI,SR and the potential barrier V 0 of the rotation from 13C relaxation measurements at fixed temperature (38~ T1,sR = 25.61 (1 + 0.382 V0), (5) where T1.sR is given in seconds and V 0 is the barrier height in kilocalories per mole, determined by microwave spectroscopic methods. The relation is remarkable in view of the variety of compounds involved, with reported barriers as high as 5.4 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the dependence of the electron spin relaxation rate due to the modulation of the hfi anisotropy is proportional to the solvent viscosity, whereas it is inversely proportional to the viscosity in the case of relaxation due to spin-rotation interaction [3]. Recently, it has been shown that in going to very low magnetic fields the electron spin relaxation due to the modulation of the hfl anisotropy should go to zero [4], whereas electron spin relaxation due to spinrotation interaction should increase twice [5,6]. Thus, knowledge of the dominating electron spin relaxation mechanism is of great importante in the data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…13,16,18,19 However, the time resolution of traditional CIDNP is limited by the duration of rf-pulse in NMR and as a rule cannot exceed 1 ms. A modified version of TR CIDNP has been developed recently. [20][21][22][23] The technique is called CIDNP in a switched external magnetic field (SEMF CIDNP) and it allows the measurements of rate constants of radical reaction with a much higher time resolution while keeping the information about reaction products. In this method, 20 after a reaction has been initiated with a laser pulse, CIDNP is formed during a variable time delay t in a first (low) magnetic field B 1 of a separate magnet, and then, after switching, CIDNP formation continues in a second (low) field B 2 for a fixed time t 0 .…”
Section: Introductionmentioning
confidence: 99%
“…The method has been successfully applied to study recombination of radical pairs in micellar solutions, 21 and to investigate short-lived neutral radicals and ion-radical pairs in homogeneous solutions. 22 This paper deals with SEMF CIDNP measurements of the rate constants of the coupling of several alkyl radicals (Scheme 1) with the persistent nitroxyl radical TEMPO (2,2,6,6-tetramethylpiperidinyl-N-oxyl). Chemical behaviour, reaction rate constants and ESR parameters of radicals shown in Scheme 1 are known for the most part.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14]. Previously, Chemically Induced Dynamic Electron Polarization (CIDEP) [15,16] and CIDNP and its modification (CIDNP with fast switching of magnetic field) have been used in NMP research to measure the rate constants of coupling between acrylate-type radicals and the persistent nitroxide [17,18]. In those experiments, the carbon centered radicals under investigation were generated by the photolysis of ketone precursors in the presence of persistent nitroxides.…”
Section: Scheme 1 the Mechanism Of Nmp With Side Reactions Of H-atommentioning
confidence: 99%